Analisis Modifikasi Desain pada Lokomotif CC-201 Tipe GE U18C dengan Metode Simulasi CFD - Fahmi Ahmad Yulianto; Riyan Ariyansah; Goodman Octavianus (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
The CC-201-type U18C locomotives are widely used for public transportation in Indonesia. Like other modes of transportation or vehicles, the body's design is an important factor to consider because it influences the aerodynamic capabilities of the vehicle. The study aims to analyze the effect of variations in the design angle of the CC-201 type U18C locomotive body on the coefficient of drag and aerodynamics. The method used in this research is CFD simulation using CAE-based engineering software, Ansys Fluent R2 2022. CFD simulations were performed on locomotive body designs with angle variations of 90°, 135°, and 150° using the same boundary condition parameters. The results show that the locomotive body design with the 60° variation has the smallest drag coefficient value of 0.51076379. The study conclusion explains that changing the angle of 150 degrees at the top of the GE U18C-type locomotive body has a significant effect on lowering the value of the drag coefficient by up to 29%.